Impact of smoking on peripheral hand microcirculation by nailfold capillaroscopy in rheumatoid arthritis patients - Salwa Galal Moussa; Mona Mansour Hasab Elnaby; Rehab Ali Ibrahim; Rasha Mohamed Hassan; Youssy Saeed Gergius (Egyptian Rheumatology and Rehabilitation)
Abstract Background Rheumatoid arthritis is a chronic multisystem autoimmune disease. The significance of nailfold capillaroscopy in evaluating microvascular changes in rheumatoid arthritis has been identified, especially when considering risk factors such as smoking. Our aim was to examine the nailfold capillaroscopy findings in rheumatoid arthritis (RA) patients and explore their relationship with smoking, with the goal of determining whether active or passive smoking could influence microvascular circulation as assessed by this tool. Results Significant differences between both smokers and non-smokers (RA) groups (P < 0.05) as regards capillary loop diameter, density, tortuosity, crossed capillaries, presence of subpapillary venous plexus, decrease of blood flow velocity, and scleroderma pattern were noted. When passive (RA) smokers were compared to non-smoker RA patients, still significant differences were noted regarding minimum capillary diameter, capillary density, increased tortuosity, and crossed capillaries besides visibility of venous plexus that were more common in passive smokers than non-smoker RA controls. Significant differences were observed for density, tortuosity, visible venous plexus, abnormal blood flow velocity, and scleroderma pattern (P < 0.05) more in active smokers than passive smokers. Regarding the smokers’ group (active and passive), a statistically significant relation (P < 0.05) was found between duration of smoking and the nailfold capillaroscopy parameters as regards capillary density, capillary tortuosity, and microhemorrhages. There was also a statistically significant positive relation (P < 0.05) between number of smoked cigarettes per day, in the smokers’ group, and the nailfold capillaroscopy parameters as regards capillary density, capillary tortuosity, and velocity of the blood flow. There was a positive statistically significant correlation (r = 0.562 and r = 0.701, P < 0.05) between number of cigarettes per day and the capillary loop diameters. Conclusion The nonspecific microvascular changes in RA are well known; however, they are more significant in the RA smoker group (whether active or passive). More intense changes were observed in the active smokers versus the passive smokers that could simulate the scleroderma pattern in some active smokers. Even the passive RA smoker group has a significant affection when compared to RA group not exposed to smoking emphasizing the deleterious effect of smoking on microcirculation even in its passive form.